2016
DOI: 10.1002/jbm.b.33787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osteoporosis on fixation of osseointegrated implants in rats

Abstract: The effect of osteoporosis on implant osseointegration has been widely investigated, whereas osteoporosis may also newly occur in patient with previously osseointegrated implant. This study was designed to investigate the effect of osteoporosis on implant fixation in rats after successful osseointegration had been obtained. Seventy female Sprague-Dawley rats were included, and each animal received two titanium implants in the distal metaphysis of femur bilaterally. Eight weeks later, ten rats were sacrificed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…Dental implants were placed in a period ranging between 21 and 182 days after osteoporosis induction in 82.9% of the included studies. In a few studies, implants were placed 56 days, 60 days, 84 days and 168 days before osteoporosis induction, while in 2 studies, they were placed at the time of osteoporosis induction. Only in 1 study, the time of implant placement was not clearly defined .…”
Section: Resultsmentioning
confidence: 99%
“…Dental implants were placed in a period ranging between 21 and 182 days after osteoporosis induction in 82.9% of the included studies. In a few studies, implants were placed 56 days, 60 days, 84 days and 168 days before osteoporosis induction, while in 2 studies, they were placed at the time of osteoporosis induction. Only in 1 study, the time of implant placement was not clearly defined .…”
Section: Resultsmentioning
confidence: 99%
“…It is well accepted that osteopenic animals display reduced peri‐implant bone volume when compared to control groups (see Fig. c) . Likewise, those animals have deteriorated peri‐implant bone microarchitectures.…”
Section: Influence Of Osteoporosis On Bone Regenerationmentioning
confidence: 89%
“…2c). 49,54,58,[63][64][65][66] Likewise, those animals have deteriorated peri-implant bone microarchitectures. 51,64,67 Clearly, structurally deteriorated bones have a negative biomechanical impact on implant anchorage.…”
Section: Microstructural Modification Of Peri-implant Bonementioning
confidence: 99%
“…The definition of OI is "direct structural and functional connection between living bone and the surface of an artificial implant" (Brånemark, Brånemark, Rydevik, & Myers, 2001). The environmental factors include loading conditions, host bone properties, interface distance, the concentration of local osteoblast and osteoclast, and systemic illness (diabetes, rheumatoid arthritis, and smoking) (Annibali, Pranno, Cristalli, la Monaca, & Polimeni, 2016;Li, He, Hua, & Hu, 2017;Shibamoto et al, 2018). It is demonstrated that the OI process can be influenced by a variety of factors, which might be generally divided into two aspects: the environment of the bone-implant interface and the design of the implant itself.…”
mentioning
confidence: 99%
“…It is demonstrated that the OI process can be influenced by a variety of factors, which might be generally divided into two aspects: the environment of the bone-implant interface and the design of the implant itself. The environmental factors include loading conditions, host bone properties, interface distance, the concentration of local osteoblast and osteoclast, and systemic illness (diabetes, rheumatoid arthritis, and smoking) (Annibali, Pranno, Cristalli, la Monaca, & Polimeni, 2016;Li, He, Hua, & Hu, 2017;Shibamoto et al, 2018). The second aspect consists of materials; surface coating; topology; macro-, micro-, and nanostructure of the implants, and so on.…”
mentioning
confidence: 99%